Autodidacticism and Music: Do Self-Taught Musicians Exhibit the Same Auditory Processing Advantages as Formally Trained Musicians? - Zendel, Benjamin Rich; Alexander, Emily J. (Frontiers in Neuroscience, 2020)
Multiple studies have demonstrated that musicians have enhanced auditory processing abilities compared to non-musicians. In these studies, musicians are usually defined as having received some sort of formal music training. One issue with this definition is that there are many musicians who are self-taught. The goal of the current study was to determine if self-taught musicians exhibit different auditory enhancements as their formally trained counterparts. Three groups of participants were recruited: formally trained musicians, who received formal music training through the conservatory or private lessons; self-taught musicians, who learned to play music through informal methods, such as with books, videos, or by ear; non-musicians, who had little or no music experience. Auditory processing abilities were assessed using a speech-in-noise task, a passive pitch oddball task done while recording electrical brain activity, and a melodic tonal violation task, done both actively and passively while recording electrical brain activity. For the melodic tonal violation task, formally trained musicians were better at detecting a tonal violation compared to self-taught musicians, who were in turn better than non-musicians. The P600 evoked by a tonal violation was enhanced in formally trained musicians compared to non-musicians. The P600 evoked by an out-of-key note did not differ between formally trained and self-taught musicians, while the P600 evoked by an out-of-tune note was smaller in self-taught musicians compared to formally trained musicians. No differences were observed between the groups for the other tasks. This pattern of results suggests that music training format impacts auditory processing abilities in musical tasks; however, it is possible that these differences arose due to pre-existing factors and not due to the training itself.